PENGARUH PEMBERDAYAAN PSIKOLOGIS, PERILAKU KERJA INOVATIF DAN KAPABILITAS TERHADAP KINERJA KARYAWAN PERUMDA TIRTA HIDAYAH BENGKULU - Yunitasari, Shinta Angelina (Managament Insight: Jurnal Ilmiah Manajemen, 2025)
This research was conducted at Perumda Tirta Hidayah Bengkulu. The main objective of this research is. 1) Testing the effect of Psychological Empowerment variable on the performance of Perumda Tirta Hidayah Bengkulu employees. 2) Testing the effect of the Innovative Work Behavior variable on performance of employees of Perumda Tirta Hidayah Bengkulu. 3) Testing the effect capability on the performance of the employees of Perumda Tirta Hidayah Bengkulu. This research is a quantitative research using secondary data and primary data collected through a list of questionnare. The sample in this study were 163 employees of Perumda Tirta Hidayah Bengkulu taken by sampling sensus. The analytical tool used is SPSS22.0 software. validity test, reliability test, t test, and hypothesis testing. The results of this study are; 1). Psychological Empowerment has a positive impact and significant effect on the performance of employees of Perumda Tirta Hidayah Bengkulu. The higher it is psychological empowerment of employees in the workplace, the higher employee performance; 2). Innovative Work Behavior has a positive and significant influence affect the performance of employees of Perumda Tirta Hidayah Bengkulu. The higher the innovative work behavior in the workplace, the higher the employee's performance; 3). Capabilities have a positive impact and significant effect on the performance of employees of Perumda Tirta Hidayah Bengkulu. The higher the capabilities possessed by employees at work, the higher the performance that will be generated. Keywords: Capabilities, Innovative Work Behavior, Performance, Psychological Empowerment.